### Solving u_tt - u_xxxx = f(t,x) by modifying biharmonic demo.

83
views
0
5 weeks ago by
I'm trying to solve the following PDE:
$u_{tt}-u_{xxxx}=f\left(t,x\right)$uttuxxxx=ƒ (t,x)
with boundary conditions in space:
$u\left(t,0\right)=u\left(t,1\right)=0$u(t,0)=u(t,1)=0
$u_{xx}\left(t,0\right)=u_{xx}\left(t,1\right)=0$uxx(t,0)=uxx(t,1)=0
and Neumann boundary conditions in time:
$u_t\left(0,x\right)=g_0\left(x\right)$ut(0,x)=g0(x)  ,   $u_t\left(1,x\right)=g_1\left(x\right)$ut(1,x)=g1(x)

I'm trying to modify the biharmonic demo, but don't know how to properly treat the time variable.
I'm not an expert in FEM, my question may lack of basic knowledges, sorry. Any advice and suggestion are welcome. Thanks.

Here's what I got so far:
from fenics import *
import numpy as np

# Optimization options for the form compiler
parameters["form_compiler"]["cpp_optimize"] = True
parameters["form_compiler"]["optimize"] = True

# Make mesh ghosted for evaluation of DG terms
parameters["ghost_mode"] = "shared_facet"

# Create mesh and define function space
mesh = UnitSquareMesh(32, 32)
V = FunctionSpace(mesh, "CG", 2)

# Define Dirichlet boundary
def boundary(x):
return near(x[1], 0.0) or near(x[1], 1.0)

# Define boundary condition
bc = DirichletBC(V, 0.0, DirichletBoundary())

# Define trial and test functions
u = TrialFunction(V)
v = TestFunction(V)

# Define normal component, mesh size and right-hand side
h = CellDiameter(mesh)
h_avg = (h('+') + h('-'))/2.0
n = FacetNormal(mesh)
f = Expression('-(pi*pi+pi*pi*pi*pi)*sin(pi*x[0])*sin(pi*x[1])', degree=2)
g = Expression('pi*sin(pi*x[0])*cos(pi*x[1])', degree=2)

# Penalty parameter
alpha = Constant(8.0)

# Define bilinear form
a = ( inner(u.dx(0),v.dx(0)) + inner(u.dx(1).dx(1), v.dx(1).dx(1)) )*dx \

# Define linear form
L = -f*v*dx + g*v*ds(0)

# Solve variational problem
u = Function(V)
solve(a == L, u, bc)
Community: FEniCS Project

0
5 weeks ago by
You can always discretize the second-order time derivative with one of the finite difference methods:

• backward difference:
$\frac{\partial^2 u^n}{\partial t^2} \approx \frac{\partial}{\partial t} \left( \frac{u^n - u^{n-1}}{\Delta t} \right) = \frac{1}{\Delta t} \left( \frac{\partial u^n}{\partial t} - \frac{\partial u^{n-1}}{\partial t} \right) \approx \frac{1}{\Delta t} \left( \frac{u^n - u^{n-1}}{\Delta t} - \frac{u^{n-1} - u^{n-2}}{\Delta t} \right) = \frac{u^n - 2 u^{n-1} + u^{n-2}}{(\Delta t)^2}$
• forward difference:
$\frac{\partial^2 u^n}{\partial t^2} \approx \frac{\partial}{\partial t} \left( \frac{u^{n+1} - u^n}{\Delta t} \right) = \frac{1}{\Delta t} \left( \frac{\partial u^{n+1}}{\partial t} - \frac{\partial u^n}{\partial t} \right) \approx \frac{1}{\Delta t} \left( \frac{u^{n+2} - u^{n+1}}{\Delta t} - \frac{u^{n+1} - u^n}{\Delta t} \right) = \frac{u^{n+2} - 2 u^{n+1} + u^n}{(\Delta t)^2}$
• central difference:
$\frac{\partial^2 u^n}{\partial t^2} \approx \frac{\partial}{\partial t} \left( \frac{u^{n+1/2} - u^{n-1/2}}{\Delta t} \right) = \frac{1}{\Delta t} \left( \frac{\partial u^{n+1/2}}{\partial t} - \frac{\partial u^{n-1/2}}{\partial t} \right) \approx \frac{1}{\Delta t} \left( \frac{u^{n+1} - u^n}{\Delta t} - \frac{u^n - u^{n-1}}{\Delta t} \right) = \frac{u^{n+1} - 2 u^n + u^{n-1}}{(\Delta t)^2}$